Management of Pulse Beetle in Green Gram Seed Using Modified Atmosphere - Durga, K. Kanaka; Sowmya, T.; Venkateshwaran, Kamala; Keshavulu, K.; Vidyasagar (International Journal of Bio-resource and Stress Management, 2022)
The experiment was conducted at Seed Research and Technology Center, PJTSAU, Rajendranagar, Hyderabad, Telangana State, India during June, 2019 under laboratory conditions using modified atmosphere with elevated levels of CO2 in two varieties of green gram namely LGG-460 and LGG-407. The study indicated that biological parameters of the test insect and the seed quality parameters were highly influenced by different levels of CO2 and storage intervals and varied between the two accessions of green gram. Emergence of adults decreased with increased concentrations of CO2. Among the two accessions, LGG-460 had least adult emergence with comparatively less insect damage than LGG-407. Higher concentrations of CO2 (45%) significantly reduced the per cent insect infestation and weight loss of both the accessions. The efficacy of different concentrations of CO2 on seed infestation and population build up revealed that exposing the bruchid infested green gram seed to 45% and higher concentrations of CO2 not only checked seed infestation but also checked the progeny production of the pest even after prolonged periods of storage up to 2 MAS. The green gram seeds stored in CO2 rich atmosphere also maintained seed quality with high germination percentage and seedling vigor up to 2 MAS. Two months storage period was effective for control of insect infestation and weight loss. Among the 2 accessions, seedling vigour I and II were found to be high in LGG 460 even at 6 months storage interval.